Characterization and clonal representation of MRSA strains in Tuzla Canton, Bosnia and Herzegovina, from 2009 to 2017 - Fatima Numanović; Urška Dermota; Jasmina Smajlović; Sandra Janežič; Nijaz Tihić; Zineta Delibegović; Amela Bećirović; Edina Muratović; Merima Gegić (Medicinski glasnik, 2020)
Aim: To characterize methicillin-resistant S. aureus (MRSA) strains phenotypically and genotypically and to determine their clonal affiliation, representation and antibiotic resistance profile. Methods: A total of 62 randomly selected MRSA isolates of different clinical samples collected from 2009 to 2017 were phenotypically and genotypically analysed. Phenotypic analyses were performed by standard microbiological procedures, and using VITEK 2/AES instrument as well as MALDI-TOF (matrix-assisted laser desorption/ionization) technology. Genotypic characterization included spa, MLST (multilocus sequence typing) and SCCmec typing, and detection of the Panton-Valentine leukocidin (PVL) and other enterotoxin encoding genes. Results: The largest number of isolates, 21 (33.87%) belonged to ST228-MRSA-I, spa type t041, t1003 and t001. Other major clones were: ST239-MRSA-III, spa type t037 and t030 (27.41%); ST8-MRSA-IV, spa type t008 and t121 (12.9%); ST247-MRSA-I, spa type t051 (4.83%). PVL was detected in 10 isolates (SCCmec IV/V). During 2009 and 2010 the most frequent MRSA strain was South German clone, ST228-MRSA-I (80% and 90%, respectively), while in later years it was replaced with Brazilian-Hungarian clone ST239-MRSA-III (75% in 2015 and 2016). The South German clone, spa type t041 in 90.48% of cases was resistant to clindamycin, ciprofloxacin, erythromycin, cefoxitin, gentamicin, kanamycin, tobramycin and penicillin, while 70.58% samples of the Brazilian-Hungarian clone spa type t037 were additionally resistant to tetracycline and rifampicin. Conclusion: This research can supplement the existing knowledge about the clonal distribution of MRSA in Bosnia and Herzegovina and their sensitivity to antibiotics in order to improve the national control of these infections
Keywords: antibiotic resistance; multi-locus sequence typing (MLST); SCCmec; spa typing